Neoadjuvant everolimus in renal angiomyolipoma with or without tuberous sclerosis complex: Results from a multicenter, retrospective study - Ruopeng Su; Tingxuan Huang; Liangyou Gu; Yige Bao; Zhihong Liu; Pinghong Dao; Lin Yao; Xiaoyi Hu; Guanghou Fu; Jitao Wu; Thibault Tricard; Guangyu Wu; et al. (Cancer Medicine)
Abstract Objectives To assess the efficacy and safety of preoperative neoadjuvant everolimus in renal angiomyolipomas (AML) patients with or without Tuberous Sclerosis Complex (TSC). Materials and Methods This multi‐institutional retrospective study enrolled renal AML patients who underwent partial nephrectomy (PN) or total nephrectomy after receiving at least 1 month of pre‐operative everolimus. Imaging evaluations were collected before and after treatment, along with demographic, surgical, and follow‐up information. The primary outcome was tumor volume reduction of ≥25%, with additional outcomes including recurrence, perioperative outcomes, renal function, and safety. Results From January 2015 to July 2022, 68 renal AML patients were studied—41 with TSC and 27 without. During everolimus treatment, 61.0% (25/41) of TSC patients and 44.4% (12/27) of non‐TSC patients achieved tumor reduction of ≥25%. Additionally, 41.5% (17/41) of TSC patients and 18.5% (5/27) of non‐TSC patients achieved a ≥ 50% reduction. Three TSC patients and 1 non‐TSC patient discontinued treatment due to side‐effects. Most patients (92.7% TSC, 85.2% non‐TSC) underwent PN. After everolimus treatment, the necessary total nephrectomy decreased to 41.2% (7/17) from baseline. Postoperatively, 1 grade 3 and 3 grade 2 complications occurred, with no grade 4 or 5 complications. After a median follow‐up of 24 months, only 1 TSC patient recurred with a diameter >3 cm. Retrospective nature is the major limitation of this study. Conclusion Everolimus was effective and well‐tolerated in neoadjuvant treatment for renal AML, especially in TSC patients. This neoadjuvant combination strategy of everolimus and PN could effectively controls recurrence and preserves renal function.